The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015 11th Conference on Ph.D. Research in Microelectronics and Electronics (PRIME) 2015
DOI: 10.1109/prime.2015.7251413
|View full text |Cite
|
Sign up to set email alerts
|

Effects of autonomic nervous system on the quality of non-invasive blood diagnosis by PPG-based sensor system

Abstract: The collection of photoplethysmography (PPG) signals from optical based sensor probe has been used extensively for the monitoring of heart rate (HR), respiration rate and oxygen saturation (SpO 2 ). Prior research by the Optical Fibre Sensor Research Group has extended the information provided by PPG based devices from monitoring HR and SpO 2 to include total haemoglobin concentration (Hb). Research presented here demonstrates that PPG signals are severely influenced by the autonomic nervous system (ANS) varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…PPG sensors can measure spectral absorption of haemoglobin derivatives non-invasively and in real time [1,2,3,4,5,6]. PPG sensor devices normally consist of one or several remote sensor units for signal collection (e.g., finger sensor probe) and a central control unit for processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPG sensors can measure spectral absorption of haemoglobin derivatives non-invasively and in real time [1,2,3,4,5,6]. PPG sensor devices normally consist of one or several remote sensor units for signal collection (e.g., finger sensor probe) and a central control unit for processing.…”
Section: Introductionmentioning
confidence: 99%
“…PPG sensor devices normally consist of one or several remote sensor units for signal collection (e.g., finger sensor probe) and a central control unit for processing. Prior research by some of the authors of this investigation has demonstrated promising application of a custom designed PPG sensor device in monitoring heart rate (HR), oxygen saturation (SpO 2 ) and total haemoglobin concentration (Hb) [3,4]. However, a drawback of this technology has been that the PPG signal is easily affected by motion artifact [5,6,7,8,9,10,11], requiring the subject (patient) to be motionless and lying or sitting down.…”
Section: Introductionmentioning
confidence: 99%